The Effect of Playing With Plasticine On Children's Creativity - Nur Zainab Buntaran; Durrotunnisa; Sri Nurhayati; Besse Nirmala; Masria Balike; Lubna Syarif; Melinda (Universitas Al-Hikmah Indonesia, 2026)
Creativity is a fundamental ability that needs to be developed from early childhood because it plays an important role in supporting intelligence and problem-solving skills. However, the reality in the field shows that the creativity of children in group B1 of Idhata Kindergarten Palu City is still relatively low. This study aims to analyze the effect of playing with plasticine on improving children's creativity. The study used a quantitative approach with a quasi-experimental one-group pretest-posttest design. All 15 children in group B1 (9 boys and 6 girls) were the research subjects. Data collection techniques included observation, interviews, and documentation. The data were analyzed descriptively and inferentially using the t-test. The results showed a significant increase in children's creativity after being given the plasticine playing treatment. Before the treatment, the percentage of children in the Very Well Developed category was 0%, Developing as Expected 7%, Starting to Develop 77.7%, and Not Developed 15.3%. After the treatment, there was an increase with percentages of Very Well Developed 38%, Developing as Expected 51%, Starting to Develop 11%, and Not Developed 0%. The t-test results showed a calculated t value of -15.250 with a significance of 0.001 (<0.05). These findings confirm that playing with plasticine has a positive effect on children's creativity. The implications of this study emphasize the importance of using plasticine play media as a strategy for stimulating creativity in early childhood education institutions.